Validation of microsatellite markers for assisted selection of soybean genotypes resistant to powdery mildew - Demore, Paula Dos Santos [UNESP]; Unêda-Trevisoli, Sandra Helena [UNESP]; Di Mauro, Antonio Orlando [UNESP]; Morceli, Thaiza Galhardo Silva [UNESP]; Muniz, Franco Romero Silva [UNESP]; Costa, Marcelo Marchi [UNESP]; Sarti, Daniela Garcia Penha [UNESP]; Mancini, Melina Cristina [UNESP] (My University, 2009)
Powdery mildew is one of the most serious diseases of soybean and is found in all producing countries. The purpose of this study was to validate microsatellite markers previously identified as associated with resistance to powdery mildew in soybean. The study was conducted in two F2 parent populations with contrasting resistance to powdery mildew. In the analysis 10 SSR primers were used for the populations, and four polymorphic markers were identified for cross 1 (MGBR95-20937 x IAC-Foscarin 31) and three for cross 2 (MGBR-46 x EMBRAPA 48). The Chi-square analysis of the phenotypic evaluation confirmed the expected segregation (3:1) of a dominant gene related to resistance. The polymorphic markers also segregated as expected (1:2:1). The markers Sat-366 and Sat-393 in the crosses 1 and 2, respectively, located at 9.41 and 12.45 cM from the gene, were considered promising for marker-assisted selection for resistance to powdery mildew in soybean, at a selection efficiency of 92.7% and 60.3% respectively.
Keywords: Bulked Segregant Analysis; Erysiphe diffusa; Glycine max; Marker-Assisted Selection